Two-component adhesive, cured film, and method for producing the cured film

The two-dose adhesive system, featuring a combination of epoxy and amine-based curing agents with hydrophilic silica and amide bonds, addresses the challenges of impregnation, construction, and transparency in reinforcing structure surfaces with fiber materials, achieving effective reinforcement and peeling prevention.

JP7671170B2Active Publication Date: 2025-05-01DENKA CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021057968
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-05-01
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Existing adhesives used to reinforce structure surfaces with fiber materials face challenges in achieving high impregnation and construction properties while maintaining transparency to visually detect deterioration and cracks.

Method used

A two-dose adhesive system comprising a first agent with an epoxy compound and a second agent with an amine-based curing agent, both containing hydrophilic silica with an average particle size of 5 to 15 nm, and a compound with an amide bond, which enhances impregnation, construction, and transparency.

Benefits of technology

The two-dose adhesive system excels in impregnation and construction properties on fiber materials, forms a hardened body with high transparency, and effectively prevents peeling from structure surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671170000001
    Figure 0007671170000001
  • Figure 0007671170000002
    Figure 0007671170000002
  • Figure 0007671170000003
    Figure 0007671170000003
Patent Text Reader

Abstract

To provide a two-pack adhesive that is excellent in impregnation to fibrous material and applicability and can form a cured body having high transparency.SOLUTION: A two-pack adhesive contains a first agent containing an epoxy compound, and a second agent containing an amine curing agent. At least one of the first agent and the second agent contains hydrophilic silica with an average particle size of 5-15 nm, and the second agent contains a compound having an amide bond (A).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a two-part adhesive, a cured film formed from the two-part adhesive, and a method for making the cured film using the two-part adhesive. [Background technology]

[0002] Conventionally, various measures have been taken to prevent materials from falling off structures such as tunnels and bridges. For example, Patent Document 1 describes a method for preventing concrete from falling off, characterized by forming a high-strength coating film on the concrete surface. Patent Document 3 describes a reinforcement coating method for reinforcing the surface of a concrete structure by forming a coating layer containing a continuous glass fiber sheet. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-15329 A [Patent Document 2] JP 2010-1707 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a composite of an adhesive and a fiber material is used as a cured film for reinforcing the surface of a structure, the adhesive is required to have high impregnation ability into the fiber material and high applicability to wall surfaces, ceiling surfaces, etc.

[0005] Furthermore, the cured film that reinforces the surface of a structure must have high transparency to allow deterioration, cracks, etc. of the base (surface of the structure) to be visually observed.

[0006] Therefore, an object of the present invention is to provide a two-component adhesive that is excellent in impregnation and application properties for fiber materials and can form a cured product having high transparency. Another object of the present invention is to provide a cured film formed from the two-component adhesive and a method for producing the cured film. [Means for solving the problem]

[0007] One aspect of the present invention relates to a two-component adhesive comprising a first component containing an epoxy compound and a second component containing an amine-based curing agent, in which at least one of the first and second components contains hydrophilic silica having an average particle size of 5 to 15 nm, and the second component contains a compound (A) having an amide bond.

[0008] In one embodiment, when the total amount of solids in the first agent and the second agent is taken as 100 mass %, the content of the hydrophilic silica may be 0.1 mass % or more and 5.5 mass % or less.

[0009] In one embodiment, the second agent may contain, as the compound (A), an amine-based curing agent (A-1) having an amino group and an amide bond.

[0010] In one embodiment, when the total amount of solids in the first agent and the second agent is taken as 100 mass %, the content of the amine-based curing agent (A-1) may be 2 mass % or more and 200 mass % or less.

[0011] In one embodiment, the second agent may contain a thixotropic agent (A-2) as the compound (A).

[0012] In one embodiment, when the total amount of solids in the first agent and the second agent is taken as 100 mass%, the content of the thixotropic agent (A-2) may be 0.1 mass% or more and 5.5 mass% or less.

[0013] In one embodiment of the two-component adhesive, the first component may contain the hydrophilic silica.

[0014] In one embodiment, the epoxy compound may include a compound represented by formula (1-1). [ka] [In the formula, p represents an integer of 0 or more, and R 11 and R 12 R each independently represents a hydrogen atom, an optionally substituted alkyl group having 1 to 5 carbon atoms, or an optionally substituted phenyl group. 11 When there are multiple R 11 may be the same or different. 12 When there are multiple R 12 may be the same or different.]

[0015] In one embodiment, the content of the hydrophilic silica may be 50 mass % or more based on the total amount of the filler in the first agent and the second agent.

[0016] In one embodiment, the mixture of the first agent and the second agent may exhibit a thixotropic index of 3.0 or greater.

[0017] In one embodiment, the cured product of the mixture of the first agent and the second agent may have a total light transmittance per mm of thickness of 80% or more.

[0018] The two-component adhesive according to one embodiment may be an adhesive for forming a cured film on the surface of a structure.

[0019] In one embodiment, the cured film may be composed of a composite of a cured mixture of the first agent and the second agent and a fiber material.

[0020] In one embodiment, the structure surface may be a concrete surface or a mortar surface.

[0021] Another aspect of the present invention relates to a cured film formed using the two-component adhesive, the cured film comprising a cured product of a mixture of the first component and the second component.

[0022] The cured film according to one embodiment may include a composite of the cured body and a fiber material.

[0023] In one embodiment, the fibrous material may be a multiaxial mesh sheet.

[0024] The cured film according to one embodiment may have a total light transmittance per mm of thickness of 70% or more.

[0025] Yet another aspect of the present invention relates to a method for producing a cured film using the two-component adhesive, the method comprising: a coating step of placing a mixture of the first component and the second component on a surface of a structure to form a coating film; and a curing step of curing the coating film to obtain a cured film containing a cured product of the mixture.

[0026] In one aspect, the application process may be a process of placing the mixture and a fiber material on the surface of the structure to form a coating film containing the mixture and the fiber material, and the curing process may be a process of curing the coating film to obtain a cured film containing a composite of the cured product of the mixture and the fiber material.

[0027] The structure surface may be a concrete surface or a mortar surface. Effect of the Invention

[0028] According to the present invention, there is provided a two-component adhesive that is excellent in impregnation and application properties for fiber materials and can form a cured product having high transparency. Also, according to the present invention, there is provided a cured film formed from the two-component adhesive and a method for producing the cured film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Preferred embodiments of the present invention will now be described in detail.

[0030] <Two-component adhesive> The two-component adhesive of this embodiment includes a first component containing an epoxy compound and a second component containing an amine-based curing agent. In this embodiment, at least one of the first and second components contains hydrophilic silica having an average particle size of 5 to 15 nm. In this embodiment, the second component contains a compound (A) having an amide bond.

[0031] The two-component adhesive of this embodiment is easy to mix the first and second components, and has excellent workability. In addition, the two-component adhesive of this embodiment has excellent impregnation into fiber materials and excellent workability on walls, ceilings, etc., because the mixture of the first and second components has appropriate viscosity. Furthermore, the two-component adhesive of this embodiment can form a cured film with high transparency because the cured product of the mixture of the first and second components has excellent transparency.

[0032] The reason why the two-component adhesive of this embodiment exhibits the above-mentioned effect is not necessarily limited, but the following reasons are considered. In the two-component adhesive of this embodiment, at least one of the first and second agents contains hydrophilic silica, and the second agent contains a compound (A) having an amide bond, so that in the mixture of the first and second agents, the amide bond of the compound (A) forms a hydrogen bond with a hydroxy group or an oxygen atom on the surface of the hydrophilic silica. The formation of this hydrogen bond strengthens the network structure of the hydrophilic silica, making it easier to exhibit thixotropy, and improving workability without impregnating the fiber material. In addition, it is considered that the amount of hydrophilic silica added can be suppressed, and a cured body with excellent transparency is easily formed.

[0033] The two-component adhesive of the present embodiment is capable of forming a cured film by mixing the first and second components. The two-component adhesive of the present embodiment may be provided, for example, as a two-component adhesive kit including the first component, a first container in which the first component is accommodated, the second component, and a second container in which the second component is accommodated.

[0034] The two-component adhesive of the present embodiment may be of the room temperature curing type.

[0035] When using the two-component adhesive of this embodiment, it is preferable to mix the first and second components so that the epoxy compound and the amine-based curing agent are equivalent, but the mixing ratio is not limited thereto. For example, the first and second components may be mixed so that the amount of the amine-based curing agent relative to the epoxy compound is 0.5 to 1.5 equivalents (preferably 0.8 to 1.2 equivalents).

[0036] The epoxy compound may be used alone or in combination of two or more. The epoxy compound may be a compound having one epoxy group or a compound having two or more epoxy groups. The epoxy compound preferably contains at least one compound having two or more epoxy groups.

[0037] The epoxy compound is preferably a compound having a glycidyl group as an epoxy group, that is, the epoxy compound preferably includes a compound having a glycidyl group, and more preferably includes a compound having two or more glycidyl groups.

[0038] Examples of epoxy compounds include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol A bis(polypropylene glycol glycidyl ether) ether, bisphenol A bis(polyethylene glycol glycidyl ether) ether, hydrogenated bisphenol A type epoxy resins, hydrogenated bisphenol F type epoxy resins, biphenyl type epoxy resins, urethane modified epoxy resins, rubber modified epoxy resins, alkyl glycidyl ethers, cresyl glycidyl ethers, phenyl glycidyl ethers, alkyl diglycidyl ethers, polyethylene glycol diglycidyl ethers, polypropylene glycol diglycidyl ethers, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, neopentyl glycol diglycidyl ether, and the like.

[0039] The epoxy compound preferably contains a compound represented by formula (1-1). [ka]

[0040] In formula (1-1), p represents an integer of 0 or more, and R 11 and R 12 R each independently represents a hydrogen atom, an optionally substituted alkyl group having 1 to 5 carbon atoms, or an optionally substituted phenyl group. 11 When there are multiple R 11 may be the same or different. 12 When there are multiple R 12 may be the same or different from each other.

[0041] R 11 and R 12 Examples of the substituent that the alkyl group having 1 to 5 carbon atoms may have include a fluorine atom and an alkoxy group (for example, an alkoxy group having 1 to 5 carbon atoms), and a fluorine atom is preferred.

[0042] R 11 and R 12 Examples of the substituent that the phenyl group in the formula (I) may have include a fluorine atom, an alkyl group (eg, an alkyl group having 1 to 5 carbon atoms), and an alkoxy group (eg, an alkoxy group having 1 to 5 carbon atoms).

[0043] R 11 is preferably a hydrogen atom, a methyl group, a phenyl group, or a trifluoromethyl group, more preferably a hydrogen atom or a methyl group, and even more preferably a methyl group. 11 When there are multiple R 11 may be the same or different, and are preferably the same.

[0044] R 12 is preferably a hydrogen atom, a methyl group, a phenyl group or a trifluoromethyl group, more preferably a hydrogen atom or a methyl group, and even more preferably a methyl group. 12 When there are multiple R 12may be the same or different, and are preferably the same.

[0045] R 11 and R 12 may be the same or different, and are preferably the same.

[0046] p is preferably 0 to 30, more preferably 0 to 20, and further preferably 0 to 2.

[0047] The compound represented by formula (1-1) may be, for example, a bisphenol A type epoxy resin. Examples of the bisphenol A type epoxy resin represented by formula (1-1) include "jER828" manufactured by Mitsubishi Chemical Corporation.

[0048] The ratio of the compound represented by formula (1-1) in the epoxy compound may be, for example, 25% by mass or more, preferably 30% by mass or more. The ratio of the compound represented by formula (1-1) in the epoxy compound may be, for example, 100% by mass or less, 99% by mass or less, 97% by mass or less, or 95% by mass or less.

[0049] The amine-based curing agent may be any component capable of crosslinking the epoxy compound and curing the mixture of the first agent and the second agent. The amine-based curing agent may be, for example, a compound having two or more reactive sites capable of reacting with the epoxy group in the epoxy compound. The amine-based curing agent may be used alone or in combination of two or more.

[0050] As the amine-based curing agent, a compound having an amino group (preferably a primary amino group or a secondary amino group) is preferable, and a compound having two or more amino groups (preferably a primary amino group or a secondary amino group) is more preferable.

[0051] The amine-based curing agent may be, for example, at least one selected from the group consisting of an aliphatic amine, an alicyclic amine, a modified aliphatic polyamine, a modified alicyclic amine, and a polyamidoamine, and is preferably at least one selected from the group consisting of a modified aliphatic polyamine, a modified alicyclic amine, and a polyamidoamine.

[0052] The content of the amine-based curing agent may be, for example, 2% by mass or more, preferably 10% by mass or more, and more preferably 20% by mass or more, based on 100% by mass of the total amount of solids in the first and second agents. The content of the amine-based curing agent may be, for example, 200% by mass or less, preferably 100% by mass or less, more preferably 60% by mass or less, and even more preferably 45% by mass or less.

[0053] In the two-component adhesive of this embodiment, at least one of the first and second components contains hydrophilic silica (S-1) having an average particle size of 1 to 15 nm. By adding the hydrophilic silica (S-1), the viscosity of the mixture of the first and second components can be improved while maintaining high transparency of the cured body, and dripping during coating on walls, ceilings, etc. can be suppressed.

[0054] As the hydrophilic silica (S-1), for example, hydrophilic fumed silica can be particularly preferably used.

[0055] The average particle size of the hydrophilic silica (S-1) is preferably 5 nm or more, more preferably 7 nm or more, and may be 9 nm or more or 10 nm or more. The average particle size of the hydrophilic silica (S-1) may be preferably 14 nm or less. The average particle size (primary particle size) is measured by image analysis of a transmission electron microscope.

[0056] The hydrophobicity of the hydrophilic silica (S-1) is preferably 30% by volume or less, more preferably 20% by volume or less, and may be 10% by volume or less, in terms of methanol wettability value.

[0057] As the hydrophilic silica (S-1), commercially available products may be used. Examples of commercially available hydrophilic silica (S-1) include AEROSIL 150, 200, 300, 380 (manufactured by Evonik), RHEOROSIL QS-10, QS-102, CP-102, QS-20, QS-20L, QS-30, QS-40 (manufactured by Tokuyama), WACKER HDK V15, N20, N20P, T30, T40 (manufactured by Asahi Kasei Wacker Silicone Co., Ltd.), etc.

[0058] In the two-component adhesive of this embodiment, only either the first component or the second component may contain hydrophilic silica (S-1), or both the first component and the second component may contain hydrophilic silica (S-1).

[0059] The content of hydrophilic silica (S-1) in the two-component adhesive of this embodiment may be, for example, 0.1% by mass or more, preferably 1.0% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2.0% by mass or more, when the total amount of solids in the first and second agents is taken as 100% by mass. This tends to further improve the resistance to dripping when applied to walls and ceilings. In addition, the content of hydrophilic silica (S-1) in the two-component adhesive of this embodiment may be, for example, 5.5% by mass or less, preferably 5.0% by mass or less, more preferably 4.0% by mass or less, and even more preferably 3.0% by mass or less, when the total amount of solids in the first and second agents is taken as 100% by mass. This tends to further improve the transparency for visually checking deterioration, cracks, etc. of the base (surface of the structure).

[0060] The two-component adhesive of the present embodiment may further contain a filler other than the hydrophilic silica (S-1). As the other filler, any known filler that is blended into a two-component adhesive can be used without any particular limitation.

[0061] Examples of the other fillers include organic fillers and inorganic fillers.

[0062] Examples of the organic filler include resin particles. The resin particles may be solid particles, porous particles, hollow particles, or fibrous particles. Examples of the resin particles include (meth)acrylic acid ester particles, aramid fibers, polyester fibers, and polystyrene particles.

[0063] Examples of the inorganic filler include hydrophilic silica other than the hydrophilic silica (S-1), hydrophobic silica, calcium carbonate, talc, clay, metal oxides, metal hydroxides, etc. The inorganic filler may be solid particles, porous particles, hollow particles, or fibrous particles.

[0064] The other filler is preferably an inorganic filler, and more preferably a hydrophilic silica other than the hydrophilic silica (S-1) or a hydrophobic silica.

[0065] The total content of the filler (hydrophilic silica (S-1) and other fillers) in the two-component adhesive of this embodiment may be, for example, 0.1% by mass or more, preferably 1.0% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2.0% by mass or more, when the total amount of the solid contents in the first and second agents is taken as 100% by mass. This provides effects such as improved sagging prevention when applied to wall and ceiling surfaces, improved reinforcement, and improved flame retardancy. In addition, the total content of the filler (hydrophilic silica (S-1) and other fillers) in the two-component adhesive of this embodiment may be, for example, 5.5% by mass or less, preferably 5.0% by mass or less, more preferably 4.0% by mass or less, and even more preferably 3.0% by mass or less, when the total amount of the solid contents in the first and second agents is taken as 100% by mass. This tends to further improve transparency for visually checking deterioration, cracks, etc. of the base (surface of a structure).

[0066] In the two-component adhesive of this embodiment, the proportion of hydrophilic silica (S-1) in the filler may be, for example, 50 mass% or more, preferably 60 mass% or more, more preferably 70 mass% or more, and may be 80 mass% or more, 90 mass% or more, 95 mass% or more, or 100 mass%.

[0067] In the two-component adhesive of this embodiment, the second component contains a compound (A) having an amide bond (-NH-CO-).

[0068] The molecular weight of the compound (A) may be, for example, 320 or more, or 660 or more. This tends to make the above-mentioned effects achieved by the formation of hydrogen bonds with the surface of the hydrophilic silica more pronounced.

[0069] The second agent may contain a compound (A) having an amide bond as an amine-based curing agent, or may contain a compound (A) having an amide bond as a component different from the amine-based curing agent. That is, the second agent may contain an amine-based curing agent (A-1) having an amide bond as the compound (A). The second agent may also contain a compound other than the amine-based curing agent, such as a thixotropic agent (A-2), as the compound (A).

[0070] Examples of the amine-based curing agent (A-1) include amidoamine, modified amidoamine, polyamidoamine, and modified polyamidoamine. Among these, polyamidoamine and modified polyamidoamine are preferred.

[0071] An example of the polyamidoamine is a dehydration condensate of a polycarboxylic acid having two or more carboxyl groups and a polyamine having two or more amino groups.

[0072] As the polyvalent carboxylic acid, for example, dimer acid, which is a dimer of tall oil fatty acid, is preferable.

[0073] Examples of polyamines include ethylenediamine, diethylenetriamine, triethylenetetramine, and hexamethylenepentamine, and among these, triethylenetetramine and hexamethylenepentamine are preferred.

[0074] When the second agent contains an amine-based curing agent (A-1), the content of the amine-based curing agent (A-1) may be, for example, 2% by mass or more, preferably 4% by mass or more, more preferably 6% by mass or more, based on the total amount of solids in the first agent and the second agent being 100% by mass. The content of the amine-based curing agent (A-1) may be, for example, 200% by mass or less, preferably 100% by mass or less, more preferably 60% by mass or less, and even more preferably 45% by mass or less, based on the total amount of solids in the first agent and the second agent being 100% by mass.

[0075] The second agent may contain two or more kinds of amine-based curing agents. For example, the second agent may contain an amine-based curing agent (A-1) and an amine-based curing agent other than the amine-based curing agent (A-1).

[0076] The thixotropic agent (A-2) is not particularly limited as long as it is a thixotropic agent having an amide bond, and can be appropriately selected from known thixotropic agents.

[0077] Examples of the thixotropic agent (A-2) include: For example, monoamides such as lauric acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid Y), palmitic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid KP), stearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Amide AP-1), purified stearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid 200), hydroxystearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid KH), unsaturated fatty acid amides such as purified oleic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid O-200), and purified erucic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Diamid L-200); Substituted amides such as N-stearyl stearamide (manufactured by Mitsubishi Chemical Corporation, product name Nikkaamide S), N-stearyl oleamide (manufactured by Mitsubishi Chemical Corporation, product name Nikkaamide SO1), N-oleyl stearamide (manufactured by Mitsubishi Chemical Corporation, product name Nikkaamide OS), and N-stearyl erucamide (manufactured by Mitsubishi Chemical Corporation, product name Nikkaamide SE); Methylol amides such as methylol stearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name Methylol Amide); Methylene bis-stearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Bisamide LA), ethylene bis-capric acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax C10), ethylene bis-lauric acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax L), ethylene bis-stearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax E), ethylene bis-hydroxystearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax H), ethylene bis-behenic acid amide saturated fatty acid bisamides such as N,N'-distearyl adipamide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax B), hexamethylene bisstearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZHS), hexamethylene bisbehenic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZHB), hexamethylene bishydroxystearic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZHH), and N,N'-distearyl adipic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZSA); unsaturated fatty acid bisamides such as ethylene bisoleic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax O), hexamethylene bisoleic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZHO), and N,N'-dioleyl adipic acid amide (manufactured by Mitsubishi Chemical Corporation, product name: Slipax ZOA); etc.

[0078] As the thixotropic agent (A-2), a commercially available mixture of the thixotropic agent (A-2) and other components (for example, a solvent, additives, etc.) may be used. Examples of the mixture include a polyamide solution (manufactured by Kusumoto Chemical Industries, Ltd., product name Disparlon 3900EF), a polycarboxylic acid amide solution (manufactured by Big Chemie, product name RHEOBYK-405), a polyaminoamide solution of unsaturated polycarboxylic acid (manufactured by Big Chemie, product name RHEOBYK-R607), a polyhydroxycarboxylic acid amide solution (manufactured by Big Chemie, product name RHEOBYK-7405), and a higher fatty acid amide solution (manufactured by Kyoeisha Chemical Industries, Ltd., product names TALEN 7200-20, TALEN 8200-20, TALEN 8300-20, TALEN 8700-20, TALEN BA-600, TALEN M-1020XFS, TALEN M-1021B, TALEN VA-750B).

[0079] When the second agent contains a thixotropic agent (A-2), the content of the thixotropic agent (A-2) may be, for example, 0.1% by mass or more, preferably 0.5% by mass or more, and more preferably 1.0% by mass or more, based on the total amount of solids in the first agent and the second agent being 100% by mass. This makes the above-mentioned effects more pronounced. In addition, the content of the thixotropic agent (A-2) may be, for example, 5.5% by mass or less, preferably 3.0% by mass or less, more preferably 2.5% by mass or less, and even more preferably 2.0% by mass or less. This tends to further improve the transparency for visually checking deterioration, cracks, etc. of the base (surface of the structure).

[0080] In the two-component adhesive of the present embodiment, at least a portion of the first and second components preferably contains a curing accelerator. The inclusion of the curing accelerator improves the curing properties of the mixture of the first and second components.

[0081] The curing accelerator may be any one that can accelerate the reaction between the epoxy compound and the amine-based curing agent, and any known curing accelerator may be used without any particular limitation. As the curing accelerator, for example, a monophenol compound is preferably used. As the monophenol compound, 4-tert-butylphenol is preferable.

[0082] The content of the curing accelerator in the two-component adhesive of this embodiment may be, for example, 0.05% by mass or more, preferably 0.1% by mass or more, more preferably 0.15% by mass or more, when the total amount of the solids in the first and second agents is taken as 100% by mass. This tends to further improve the curing property of the mixture of the first and second agents. In addition, the content of the curing accelerator in the two-component adhesive of this embodiment may be, for example, 30% by mass or less, preferably 25% by mass or less, more preferably 20% by mass or less, when the total amount of the solids in the first and second agents is taken as 100% by mass. This tends to ensure a longer usable time of the mixture of the first and second agents.

[0083] The two-component adhesive of the present embodiment may further contain other components in addition to those described above, such as a cure retarder, a light stabilizer, a light absorber, an antioxidant, an anti-deterioration agent, a pigment, a dye, a silane coupling agent, a defoamer, a leveling agent, a dispersant, a rheology control agent, a wax, a solvent, water, etc.

[0084] The first agent contains an epoxy compound, and may further contain a filler as necessary, and may further contain other components as necessary.

[0085] The content of the epoxy compound in the first agent may be, for example, 80 mass% or more, preferably 90 mass% or more, and may be 95 mass% or more, 97 mass% or more, or 100 mass% based on the total amount of solids in the first agent.

[0086] The viscosity of the first agent may be, for example, 1,000 mPa·s or more, and preferably 2,000 mPa·s or more. The viscosity of the first agent may be, for example, 60,000 mPa·s or less, and preferably 30,000 mPa·s or less, and more preferably 15,000 mPa·s or less.

[0087] The thixotropic index of the first agent is preferably less than 3, and more preferably 1.5 or less. This makes it easier to measure, stir, etc. when blending and mixing with the second agent. The thixotropic index of the first agent may be, for example, 1.0 or more.

[0088] The second agent contains an amine-based curing agent, and may further contain a filler as necessary, may further contain a curing accelerator as necessary, and may further contain other components as necessary.

[0089] The content of the amine-based curing agent in the second agent may be, for example, 60 mass% or more, preferably 70 mass% or more, more preferably 80 mass% or more, and may be 90 mass% or more, 95 mass% or more, or 100 mass% based on the total amount of solids in the second agent.

[0090] The viscosity of the second agent may be, for example, 1,000 mPa·s or more, and preferably 2,000 mPa·s or more. The viscosity of the second agent may be, for example, 60,000 mPa·s or less, and preferably 30,000 mPa·s or less, and more preferably 15,000 mPa·s or less.

[0091] The thixotropic index of the second agent is preferably less than 3, and more preferably 1.5 or less. This makes it easier to measure, stir, etc. when blending and mixing with the first agent. The thixotropic index of the second agent may be, for example, 1.0 or more.

[0092] In the two-component adhesive of this embodiment, the mixture of the first and second components preferably exhibits a thixotropic index of 3.0 or more (more preferably 4.0 to 8.0). In addition, in the two-component adhesive of this embodiment, the mixture of the first and second components preferably exhibits a viscosity of 2,000 mPa·s or more and 100,000 mPa·s or less (more preferably 4,000 mPa·s or more and 50,000 mPa·s or less). The viscosity and thixotropic index of the mixture of the first and second components change over time due to the reaction between the epoxy compound and the amine-based curing agent. In other words, the above definition means that the mixture of the first and second components exhibits the above viscosity and thixotropic index for a certain period of time after mixing.

[0093] In this specification, the viscosity of the first agent, the second agent, and the mixture of the first agent and the second agent refers to the viscosity measured by a cone-plate type rotational viscometer at 23° C. and 20 rpm. The thixotropic index refers to the ratio (V2 / V1) of the viscosity V2 at 23° C. and 2 rpm to the viscosity V1 at 23° C. and 20 rpm measured by a cone-plate type rotational viscometer.

[0094] In the two-component adhesive of this embodiment, the total light transmittance per mm thickness of the cured product of the mixture of the first and second components is preferably 80% or more. Note that in this specification, the total light transmittance of the cured product is measured according to JIS K7136:2000 (Plastics: Determination of haze of transparent materials) using a UV-VIS-NIR spectrophotometer SolidSpec-3700i manufactured by Shimadzu Corporation.

[0095] The two-component adhesive of the present embodiment has excellent impregnation and application properties for fiber materials, and is capable of forming a cured product with high transparency, and therefore can be suitably used as an adhesive for forming a cured film on the surface of a structure.

[0096] The cured film may be for preventing the constituent materials from peeling off from the surface of the structure. That is, the two-component adhesive of the present embodiment may be an adhesive for forming a cured film on the surface of the structure that prevents the constituent materials of the structure from peeling off.

[0097] The surface of the structure is not particularly limited, but from the viewpoint of obtaining a remarkable effect of preventing the material from peeling off, a concrete surface or a mortar surface is preferable. That is, the two-component adhesive of the present embodiment may be an adhesive for forming a hardened film on a concrete surface or a mortar surface.

[0098] The surface of the structure may be provided with an impregnated reinforcing material, a primer, a cross-section repair material, or a leveling material.

[0099] The cured film formed on the surface of the structure may include a composite of the cured product of the mixture of the first and second parts and the fiber material. That is, the two-component adhesive of the present embodiment may be an adhesive for forming a cured film on the surface of the structure, the cured film including a composite of the cured product of the mixture of the first and second parts and the fiber material.

[0100] The fiber material is not particularly limited, and any fiber material used for a composite can be used without any particular limitation. The fiber material may be, for example, glass fiber, polyester fiber, polyethylene terephthalate fiber, vinylon fiber, acrylic fiber, nylon fiber, carbon fiber, aramid fiber, etc. Among these, glass fiber is particularly preferred from the viewpoints of the harmfulness of combustion gas and the visibility of the surface of the structure after curing.

[0101] In this embodiment, the fiber material may be a multiaxial mesh sheet. Examples of the multiaxial mesh sheet include biaxially woven glass cloth. The two-component adhesive of this embodiment can form a cured film with excellent transparency, so that the base can be sufficiently visually observed even at the fiber intersection of the multiaxial mesh sheet, and the presence or absence of cracks can be easily confirmed.

[0102] <Cured film> The cured film of the present embodiment is a cured film formed using the above-mentioned two-component adhesive, and includes a cured product of a mixture of the first and second components.

[0103] The mixture of the first and second agents may be one in which the first and second agents are mixed such that the amount of the amine-based curing agent relative to the epoxy compound is 0.5 to 1.5 equivalents (preferably 0.8 to 1.2 equivalents). The mixture of the first and second agents gradually cures at room temperature to form a cured product.

[0104] The cured film of the present embodiment may include a composite of a fiber material and a cured mixture of the first and second agents. The composite may be formed, for example, by curing a mixture of the first and second agents and a fiber material, or by impregnating a fiber material with the mixture of the first and second agents and curing the mixture.

[0105] The cured film of the present embodiment may be composed, for example, of only a composite layer containing a cured body and a fiber material, or may be composed of a cured body layer containing a cured body and a composite layer containing a cured body and a fiber substrate.

[0106] The thickness of the cured film is not particularly limited, but may be, for example, 0.1 mm or more, preferably 0.4 mm or more, more preferably 0.6 mm or more, and may be, for example, 2.0 mm or less, preferably 1.2 mm or less, more preferably 1.0 mm or less.

[0107] The amount of the cured material in the cured film is, for example, 0.1 kg / m 2 or more, preferably 0.4 kg / m 2 More preferably, 0.6 kg / m 2 The amount of the cured material in the cured film is, for example, 2.0 kg / m 2 may be less than or equal to 1.2 kg / m 2 Less than or equal to 1.0 kg / m 2 The following is the result.

[0108] The amount of fibrous material in the cured membrane is, for example, 0.05 kg / m 2 or more, preferably 0.1 kg / m 2 More preferably, 0.13 kg / m 2The amount of the fiber material in the cured film is, for example, 0.35 kg / m 2 may be less than or equal to 0.30 kg / m 2 Less than or equal to 0.25 kg / m 2 The following is the result.

[0109] The cured film of the present embodiment has a total light transmittance of preferably 70% or more, more preferably 80% or more. Such a cured film allows the structure surface to be visually observed through the cured film, and therefore has the following advantages: cracks and the like on the structure surface can be easily found; peeling can be prevented while maintaining the design of the structure surface; etc.

[0110] In this specification, the total light transmittance of the cured film is measured using a UV-VIS-NIR spectrophotometer SolidSpec-3700i manufactured by Shimadzu Corporation in accordance with JIS K7136:2000 (Plastics: Determination of haze of transparent materials).

[0111] <Method of manufacturing the cured film> The cured film of the present embodiment can be produced, for example, by a production method including a coating step of placing a mixture of the first agent and the second agent on the surface of a structure to form a coating film, and a curing step of curing the coating film to obtain a cured film containing a cured product of the mixture.

[0112] In the coating step, the mixture and the fiber material may be disposed on the surface of a structure to form a coating film containing the mixture and the fiber material. By forming such a coating film, a cured film containing a composite of the cured body and the fiber material is formed.

[0113] The amount of the mixture applied to the surface of the structure is, for example, 0.1 kg / m2 in terms of the amount of solids in the mixture. 2 or more, preferably 0.4 kg / m 2 More preferably, 0.6 kg / m 2 The amount of the mixture applied to the surface of the structure is, for example, 2.0 kg / m2 in terms of the amount of solids in the mixture. 2 may be less than or equal to 1.2 kg / m2 Less than or equal to 1.0 kg / m 2 The following is the result.

[0114] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments. For example, one aspect of the present invention may be a peeling prevention method for preventing peeling of a component material from a surface of a structure. Another aspect of the present invention may be a structure having a peeling prevention cured film on at least a part of the surface. EXAMPLES

[0115] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0116] The abbreviations for the components used in the examples and comparative examples and the test methods carried out in the examples and comparative examples are as follows.

[0117] <Epoxy compounds> jER828: Bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 190, glycidyl group-containing epoxy compound) ADEKA GLYCILOR ED-523T (in the table, "ED-523T"): Neopentyl glycol diglycidyl ether (manufactured by ADEKA Corporation, epoxy equivalent 140)

[0118] <Amine-based hardener> Fujicure 8116: Modified alicyclic polyamine (manufactured by Mitsubishi Chemical Corporation, active hydrogen equivalent 72) · TOMAID 235-A: Polyamidoamine (amine-based hardener containing amide bonds, manufactured by T&K TOKA, active hydrogen equivalent 95)

[0119] <Filler> AEROSIL 200: Hydrophilic fumed silica (primary particle size 12 nm, manufactured by Evonik) AEROSIL 130: Hydrophilic fumed silica (primary particle size 16 nm, manufactured by Evonik) AEROSIL R974: Hydrophobic fumed silica (primary particle size 12 nm, manufactured by Evonik) Calcium carbonate (manufactured by Nitto Powder Industries Co., Ltd.)

[0120] <Thixotropic agent> R-607: Solution of polyaminoamide of unsaturated polycarboxylic acid (manufactured by Big Chemie): Amide AP-1: Stearic acid amide (manufactured by Mitsubishi Chemical Corporation)

[0121] <Curing accelerator> 4-tert-Butylphenol (Fujifilm Wako Pure Chemical Industries, Ltd.)

[0122] <Fiber sheet> WL 230 140 BS6: Biaxially woven glass cloth (manufactured by Nittobo)

[0123] <Viscosity measurement of adhesive composition> A cone-plate type rotational viscometer TVB-25H manufactured by Toki Sangyo was used. A No. 5 rotor was used. Viscosity was measured 5 minutes after weighing and mixing the specified amounts of the first and second agents. The amounts of the first and second agents were determined based on the epoxy equivalent and active hydrogen equivalent so that the epoxy group reacted with the active hydrogen derived from the amine in an equivalent amount. The cup temperature of the viscometer was set at 23°C, and the sample amount was 500 cm. 3 The rotation speeds were 20 rpm and 2 rpm. The measurement result at 20 rpm was taken as the viscosity of the adhesive, and the ratio of the viscosity at 2 rpm to the viscosity at 20 rpm was taken as the thixotropic index. The results are shown in Table 1.

[0124] <Calculation of total light transmittance and haze of cured film> The first and second agents were weighed out in predetermined amounts and mixed to obtain an adhesive composition. The amounts of the first and second agents were determined based on the epoxy equivalent and active hydrogen equivalent so that the epoxy group reacted with the active hydrogen derived from the amine in an equivalent amount. Next, a specified amount of coating (1.0 kg / m2) was applied onto the PET sheet. 2) and immediately after coating, a fiber sheet was placed on top and the fiber sheet was impregnated with the adhesive composition using a roller. After curing at 23°C for 7 days, the PET film was peeled off to obtain a cured film (thickness 1 mm) containing the composite. The total light transmittance and haze of the obtained cured film were measured using a Shimadzu Corporation UV-VIS-NIR spectrophotometer SolidSpec-3700i according to JIS K7136:2000 (Plastics: Determination of haze of transparent materials).

[0125] <Evaluation of background visibility using an image processing evaluation system> A black simulated crack with a width of 0.2 mm was drawn on a white substrate made of cement-based hydrated hardened material, and the specified amount of coating (1.0 kg / m 2 ) was used to coat the adhesive composition, and immediately after coating, a fiber sheet was placed on top and the fiber sheet was impregnated with the adhesive composition using a roller. After curing for 7 days at 23°C, the cured film was photographed from directly above, and the photographed image was converted to grayscale and then binarized so that the areas corresponding to the original simulated cracks were black and the areas without the simulated cracks were white. If the proportion of pixels that were actually judged to be black among the pixels corresponding to the simulated cracks was 60% or more, the visibility was rated A; if it was 30% or more but less than 60%, it was rated B; and if it was less than 30%, it was rated C.

[0126] <Evaluation of mixing ability> A red colorant was added to the first agent, and a green colorant was added to the second agent. The amounts of the first and second agents were determined based on the epoxy equivalent and active hydrogen equivalent so that the epoxy group reacted with the active hydrogen derived from the amine in an equivalent amount. The volume of the mixing cup was 5L, and the first and second agents were weighed out so that the total weight of the first and second agents was 3kg, and mixed for 30 seconds with a mixer (HiKOKI mixer UM22 + Φ180 screw; 400 rpm). After mixing, if the two agents were visually well mixed and had a uniform color appearance, it was rated A; if the coloring from each agent before mixing was visible on the walls and other parts without mixing, it was rated B; and if the coloring from each agent before mixing remained on the entire surface, it was rated C.

[0127] <Evaluation of workability> A substrate made of cement-based hydrated hardened material was set up vertically on the ground so that the construction surface was perpendicular to the ground. The construction surface and the materials and bases used in the test were kept at 23°C. The amounts of the first and second agents were determined based on the epoxy equivalent and active hydrogen equivalent so that the epoxy group reacted with the active hydrogen derived from the amine in equivalent amounts. The two liquids were thoroughly mixed with a mixer and the specified coating amount (0.6 kg / m2) was applied. 2 The adhesive composition was applied to the fiber sheet using a roller, and the fiber sheet was immediately attached after application, and the adhesive composition was impregnated into the fiber sheet using a roller. If there was no misalignment of the sheet or adhesive dripping, the test was rated A. If there was no misalignment of the sheet and adhesive dripping of less than 1 cm occurred, the test was rated B. If there was misalignment of the sheet or adhesive dripping of 1 cm or more occurred, the test was rated C.

[0128] Example 1 A first agent was obtained by mixing 90 parts by weight of jER828, 10 parts by weight of ADEKA GLYCIROL ED-523T, and 5.0 parts by weight of AEROSIL 200. Next, a second agent was obtained by mixing 36 parts by weight of Fujicure 8116, 2.0 parts by weight (amount of solution) of R-607, and 0.2 parts by weight of 4-tert-butylphenol. The first and second parts were mixed to obtain an adhesive composition. The obtained adhesive composition was evaluated by the above-mentioned method. The evaluation results are shown in Table 1.

[0129] (Examples 2 to 9) Adhesive compositions were prepared and evaluated in the same manner as in Example 1, except that the compositions of the first and second agents were changed as shown in Table 1. The evaluation results are shown in Table 1.

[0130] (Comparative Examples 1 to 6) Adhesive compositions were prepared and evaluated in the same manner as in Example 1, except that the compositions of the first and second agents were changed as shown in Table 2. The evaluation results are shown in Table 2.

[0131] [Table 1]

[0132]

Table 2

Claims

1. A two-component adhesive comprising a first component containing an epoxy compound and a second component containing an amine-based curing agent, At least one of the first agent and the second agent contains hydrophilic silica (S-1) having an average particle size of 5 to 15 nm, The second agent contains a compound (A) having an amide bond, The second agent contains a thixotropic agent (A-2) as the compound (A), When the total amount of solid contents in the first agent and the second agent is taken as 100 mass%, the content of the hydrophilic silica (S-1) is 0.1 mass% or more and 5.5 mass% or less, a total content of a filler in the two-component adhesive is 0.1% by mass or more and 5.5% by mass or less, when the total amount of solids in the first component and the second component is taken as 100% by mass; The ratio of the hydrophilic silica (S-1) in the filler is 70 mass% or more. Two-component adhesive.

2. The two-component adhesive according to claim 1, wherein the second part contains, as the compound (A), an amine-based curing agent (A-1) having an amino group and an amide bond.

3. 3. The two-component adhesive according to claim 2, wherein the content of the amine-based curing agent (A-1) is 2% by mass or more and 200% by mass or less when the total amount of solids in the first agent and the second agent is 100% by mass.

4. The content of the thixotropic agent (A-2) is 0.1% by mass or more and 5.5% by mass or less when the total amount of solids in the first agent and the second agent is 100% by mass. The two-component adhesive according to any one of claims 1 to 3.

5. The two-component adhesive according to any one of claims 1 to 4, wherein the first component contains the hydrophilic silica (S-1).

6. The two-component adhesive according to any one of claims 1 to 5, wherein the epoxy compound comprises a compound represented by formula (1-1): 【Chemistry 1】 [In the formula, p represents an integer of 0 or more, and R 11 and R 12 R each independently represents a hydrogen atom, an optionally substituted alkyl group having 1 to 5 carbon atoms, or an optionally substituted phenyl group. 11 When there are multiple R 11 may be the same or different. 12 When there are multiple R 12 may be the same or different.

7. The two-component adhesive of any one of claims 1 to 6, wherein the mixture of the first and second parts exhibits a thixotropic index of 3.0 or greater.

8. The two-component adhesive according to any one of claims 1 to 7, wherein a cured product of the mixture of the first and second components has a total light transmittance per mm thickness of 80% or more.

9. The two-component adhesive according to any one of claims 1 to 8, which is an adhesive for forming a cured film on a surface of a structure.

10. The two-component adhesive according to claim 9 , wherein the cured film is composed of a composite of a cured mixture of the first part and the second part and a fibrous material.

11. The two-component adhesive according to claim 9 or 10, wherein the structural surface is a concrete surface or a mortar surface.

12. A cured film formed using the two-component adhesive according to any one of claims 1 to 11, A cured film comprising a cured product of the mixture of the first part and the second part.

13. The cured film according to claim 12 , comprising a composite of the cured body and a fibrous material.

14. The cured membrane of claim 13 , wherein the fibrous material is a multiaxial mesh sheet.

15. The cured film according to any one of claims 12 to 14, having a total light transmittance per mm of thickness of 70% or more.

16. A method for producing a cured film using the two-component adhesive according to any one of claims 1 to 11, comprising the steps of: a coating step of applying a mixture of the first agent and the second agent to a surface of a structure to form a coating film; a curing step of curing the coating film to obtain a cured film containing a cured product of the mixture; A method for producing a cured film comprising the steps of:

17. the application step is a step of disposing the mixture and the fiber material on a surface of the structure to form a coating film containing the mixture and the fiber material, The method according to claim 16, wherein the curing step is a step of curing the coating film to obtain a cured film containing a composite of the cured product of the mixture and the fiber material.

18. The method according to claim 16 or 17, wherein the surface of the structure is a concrete surface or a mortar surface.

Citation Information

Patent Citations

  • Two-component epoxy resin adhesive and packing composition

    JP1985104173A

  • Sealing method and sealing agent

    JP1992020661A

  • Double fluid type epoxy resin adhesive, and repairing and reinforcing method of concrete construction employing the same

    JP1999020063A

  • Method for preventing peeling of concrete, and method for repairing concrete

    JP2005015329A

  • Reinforced coating method of concrete structure surface

    JP2010001707A